Solitary fibrous tumor of nasal cavity: a rare case report with review of literature - Agale, Shubhangi Vinayak; Arole, Vidya Chandrakant; Jadhav, Dipashri Bhaurao; Juvekar, Jai Vijay (International Journal of Research in Medical Sciences, 2017)
Solitary fibrous tumor is an unusual soft tissue neoplasm. Commonly the tumor is located in pleural cavity but recently has been described in many extra-thoracic locations. Nose and paranasal sinuses are rare sites for this tumor and so far less than 30 cases have been reported in the literature. In the nasal cavity the tumor usually presents as a polypoidal intranasal mass in a middle aged patient. Erosion of adjacent structures may occur but tumor does not metastasize. Local excision is almost invariably curable. We report SFT in a 50 year old patient with involvement of unilateral nasal cavity and all paranasal sinuses.